PENYULUHAN DAN PELATIHAN PENANAMAN MANGROVE DI KELURAHAN BIRA KECAMATAN TAMALANREA KOTA MAKASSAR - Tamsil, Andi; Hasnidar, Hasnidar; Akram, Andi Muhammad (JURNAL PENGABDIAN MASYARAKAT KAUNIAH, 2022)
Bira Village, Tamalanrea District, Makassar City is one of the villages that has extensive mangrove forest potential. The people of the village have a very high dependence on the mangrove ecosystem, but their understanding and concern for the importance of maintaining the mangrove ecosystem is still low, even though in Bira Village there are Community Leaders who have received the Kalpataru Award from the Government of the Republic of Indonesia. This PKM aims to increase partners' understanding of ecological and biological aspects and improve partners' skills in mangrove planting. PKM activities will be held on January 5, 2022 in Bira Village, Tamalanrea District, Makassar City. The implementation methods carried out are 1) Education about aspects of mangrove ecology; 2) Education on aspects of mangrove biology; 3) Mangrove planting training. The implementation of the service activities went smoothly and received very high appreciation by partners (Lantebung Mangrove Observer Group); Partners' skills in choosing and how to plant mangroves are improving. The community really hopes to be given assistance in a sustainable manner, not only for ecological and biological interests but also economic interests.